Prince Caspian - Lewis, C.C.; The Chronicles of Narnia (Lahore ILQA Publications, 2015)
It s been 1300 years in Narnia but only a year in England when Pevensie children return to the magical land, this time to help the fugitive Prince Caspian. Prince Caspian is the rightful heir to the throne of Narnia, currently held by the usurper Miraz, Caspian s uncle, who having dethroned and murdered his father has forced him into hiding. Will Peter, Susan, Edmond and Lucy be able to help Caspian to regain his father s throne? (3z(BPrince Caspian(3y (Bis the fourth novel in (3z(BThe Chronicles of Narnia(3y(B.s
A classic of children s fantasy literature, (3z(BThe Chronicles of Narnia(3y (Bis a series of seven stand-alone books. It is one of the most popular children series ever written. It has been translated in more than 40 languages and sold over 100 million copies around the worlds
Keywords: Fiction & Literature/ Classic Story Books A Summery Of Fun & Learning